2010
DOI: 10.1016/j.ijrobp.2010.07.337
|View full text |Cite
|
Sign up to set email alerts
|

Dose-volume Comparison of Proton Radiotherapy and Stereotactic Body Radiotherapy for Non-small Cell Lung Cancer

Abstract: position of the inhomogeneity. Margins for range uncertainties due the CT number variations were not considered in this study so as to focus only on the range changes caused by the displacement of inhomogeneity. An expanded or contracted contour of the high density or low density object was created by adding or subtracting 3 mm margin, respectively to the actual contours of the inhomogeneities (blurred image set). A single field optimization plan was created both in the original and blurred image sets for SSPB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 0 publications
0
25
1
Order By: Relevance
“…With regard to SRT, several groups reported RFs frequencies ranging from 4% to 37.7% after SRT for earlystage NSCLC; these rates were not much higher compared with those observed in our study (30.2%) (Pettersson et al 2009;Dunlap et al 2010;Andolino et al 2011;Welsh et al 2011;Asai et al 2012;Creach et al 2012;Mutter et al 2012;Stephans et al 2012;Taremi et al 2012;Nambu et al 2013). Although PBT reportedly offers advantages over SRT, it has not been reported to dramatically reduce RFs incidence (Georg et al 2008;Kadoya et al 2011).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…With regard to SRT, several groups reported RFs frequencies ranging from 4% to 37.7% after SRT for earlystage NSCLC; these rates were not much higher compared with those observed in our study (30.2%) (Pettersson et al 2009;Dunlap et al 2010;Andolino et al 2011;Welsh et al 2011;Asai et al 2012;Creach et al 2012;Mutter et al 2012;Stephans et al 2012;Taremi et al 2012;Nambu et al 2013). Although PBT reportedly offers advantages over SRT, it has not been reported to dramatically reduce RFs incidence (Georg et al 2008;Kadoya et al 2011).…”
Section: Discussioncontrasting
confidence: 71%
“…Compared with X-ray therapy, proton beam therapy (PBT) offers good dose concentration, as revealed by the characteristics of the Bragg peak, and provides advantages over SRT in terms of decreasing doses to normal tissues as well as in treating early-stage NSCLC (Georg et al 2008;Kadoya et al 2011). Kanemoto et al (2013) discussed RF following PBT for peripheral hepatocellular carcinomas, excluding central lesions, which were treated with 66 cobalt Gy equivalents [Gy; relative biological effectiveness (RBE)] in 10 fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al reported that PSPT significantly reduced dose to normal tissues and the integral dose to patients with non-small cell lung cancer (NSCLC) compared to threedimensional conformal radiation therapy (3D-CRT) and intensity modulated radiation therapy (IMRT) [2]. Kadoya et al reported that using proton beam significantly reduced Lung dose compared to stereotactic body radiation therapy (SBRT) for Stage I non-small-cell lung cancer [8]. The mean dose, V5, V10, V15, and V20 were 4.6 Gy, 13.2%, 11.4%, 10.1%, and 9.1% for proton therapy compared to 7.8 Gy, 32%, 21.8%, 15.3%, and 11.4%, respectively, for SBRT with a prescribed dose for 66 Gy.…”
Section: Dosimetric Advantagesmentioning
confidence: 99%
“…At present, whether or not PBT is superior to SBRT for early-stage lung cancer is unclear (30). However, the PBT radiation dose to normal lung tissue has been reported to be lower than the SBRT dose (31,32). T1N0M0 NSCLC is an indication for the use of SBRT using X-ray beams, but SBRT for large T2 tumors leads to a marked increase in the dose to normal lung, which may lead to increased pulmonary toxicity (33,34).…”
Section: Lung Cancermentioning
confidence: 99%